The Advent of AI-Driven Finfluencers and Automation in Financial Supervision - T. Venkatesan; Asep Muhamad Ramdan; A. Stephen (The Indonesian Institute of Science and Technology Research, 2026)
Over the past two decades, artificial intelligence (AI) has experienced rapid development and has been increasingly applied across various sectors, including finance. Alongside this technological advancement, a growing body of research has examined the use of AI-driven tools in financial services, particularly the emergence of finance influencers, commonly referred to as “finfluencers.” These actors leverage AI technologies to deliver personalized financial insights, automated investment advice, and real-time market analysis to a broad and diverse audience. AI-enabled finfluencer platforms offer advantages such as accessibility, continuous availability, data-driven recommendations, and enhanced monitoring of market trends, which appeal to investors seeking timely and customized financial guidance. However, the integration of AI and finfluencers also raises concerns related to reliability, ethical considerations, regulatory oversight, and decision-making accountability. This study aims to examine key AI applications in the financial sector, identify major finfluencer models and collaboration patterns, and discuss their implications for financial advisory practices. The paper further outlines future research directions to support responsible and effective AI-driven financial advisory systems.